Investigation on the suitability of methyl ester of crude palm oil as fuel for diesel engine - Azhar Abdul Aziz, 1959- 378745; Zainol Anuar Mohd. Sharif, supervisor 358823; Fakulti Kejuruteraan Mekanikal 8081 (1990)
Thesis (Master of Engineering (Mechanical)) - Universiti Teknologi Malaysia, 1990